PENGARUH EFISIENSI MODAL KERJA, UKURAN PERUSAHAAN DAN GROWTH OPPORTUNITY TERHADAP PROFITABILITAS BADAN USAHA MILIK DAERAH (BUMD) KOTA MAGELANG PERIODE 2015 - 2018 - Papang Permadi Prasetyo; Sulastiningsih Sulastiningsih (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to analyze the effect of working capital efficiency, company size and growth opportunity on the profitability of BUMD Kota Magelang in the 2015-2018 period. The aspects examined are working capital efficiency, company size and growth opportunity for profitability. This research is a descriptive analysis research. The population in this study was 6 BUMD. The data used are secondary data in the form of annual financial statements published by each bank. Data were analyzed using descriptive statistics, linear regression analysis, t test, F test and coefficient of determination. The results of this study indicate that: 1) The variable efficiency of working capital and growth opportunity does not affect profitability; 2) Company size variable has positive and significant effect on profitability; 3) Together working capital efficiency, company size and growth opportunity affect profitability. The magnitude of the effect of working capital efficiency, company size and growth opportunity on profitability is 53,8%, while the remaining 46,2% is influenced by other variables not observed in this study.